Potret dan Segmentasi Mad’u Dalam Perkembangan Media di Indonesia - Asna Istya Marwantika (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2019)
This article discusses portrait and segmentation of mad'u / da'wah audience in the development of media in Indonesia. Using descriptive analysis and audience concept from Dennis McQuail it was found that da'wah activities are basically always segmented, where messages and patterns of da'wah will always try to be adapted to the context of the audience. Correspondingly, da'wah activities and movements have emerged and evolved in various forms mediated by the mass media (print, radio and television) which are linear in nature and categorize the medium as a passive audience, while preaching activities mediated by new media (digital ) non-linear nature categorizes the madness as an active audience. This active category of mad'u passive-mad'u also has consequences and challenges such as the adaptation of the format of da'wah in the media, the commodification of religion, the shift of religious authority (preachers), the exposure of radicalism, it produce hoaxes, and echo chambers namely echo space that contains the views of people who think the same and one taste so it does not produce a good dialogue.